Child Care Subsidy Use and Children's Outcomes in Middle School - Wladimir Zanoni; Anna D. Johnson (SAGE Publishing, 2019)
This article examines associations between child care subsidy use in early childhood and children's middle school outcomes. Using a unique database linking administrative records of child care subsidy receipt with parental earnings, social assistance data, and students' public school outcomes, we generate quasi-experimental estimates of subsidy effects on children's reading and math test scores and school absences in third through eighth grades. Findings suggest that subsidies are associated with reduced absenteeism in seventh and eighth grades and with increased reading and math scores in third grade, but only for the subset of children whose subsidies were used to attend licensed center- or home-based care. Results provide initial evidence for longer term impacts of the child care subsidy program on children's school performance.